Value of Statistical Life Estimates for Children in Metro Manila, Inferred from Parents’ Willingness to Pay for Dengue Vaccines - Palanca-Tan, Rosalina (Archīum Ateneo, 2008)
This study presents a 'value of life' estimate for children in Metro Manila of between US$0.70 million and US$0.80 million. It was carried out by Rosalina Palanca-Tan, from the Department of Economics at the Ateneo de Manila University in Quezon City. Palanca-Tan's assessment is based on parents' willingness to pay for two hypothetical dengue vaccines for their children. It takes an innovative approach to the valuation challenge, one that removes much of the uncertainty surrounding similar past studies. This method involves isolating people's willingness to pay for the reduction in mortality risk that the vaccines bring. This is done by disentangling it from their willingness to pay for other related benefits that the vaccines bring (such as reducing the pain associated with illness). The study succeeds in producing a result that can be used generally to value life in a range of scenarios and situations. As children are most vulnerable to environmental degradation such as air pollution and water pollution, this valuation will be particularly useful to environmental policy makers and campaigners looking to estimate the overall benefit of their work.